Amir Temur's Timurid-Era Garden Design - Malapaka, Indira (Journal of Progress in Civil Engineering, 2025)
The theme of Timurid gardening art was widely studied by a decade of scientists from the Soviet and post-Soviet space. However, the opinions of authoritative scientists regarding the historical location of the Bagi Dilkusho garden remained ambiguous and contradictory. The main goal of this research is to identify the historical location of the disappeared garden of Amir Temur - “Bagi Dilkusho”, in order to develop a project proposal for its architectural revival.